A clinical study to determine metformin as a cause of serum vitamin B12 decrease and effect of combination of metformin and mecobalamin on serum vitamin B12 levels in type 2 diabetics - Kiran, Mayuresh D.; Naik, Bhagyashree N. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Several evidences show metformin decreases vitamin B12. Diabetics are also at the risk of developing neuropathy which is treated with vitamin B12. metformin being initial therapy for diabetic patients, it becomes all the more important to know the extent of this decrease. The study was designed with the objective to compare the levels of vitamin B12 in patients on metformin vis-à-vis on antidiabetic drugs other than metformin and to evaluate the increase in vitamin B12 levels after prescribing a combination of metformin and mecobalamin, in T2DM patients. Methods: Of 500 enrolled, 321 patients completed the study for duration of 6 months, divided in two periods of 3 months each. At the end first period of 3 months the vitamin B12 levels were compared form Metformin vs. that of other antidiabetics. In second period of 3 months a combination of metformin and mecobalamin was given instead of plain metformin and vitamin B12 levels were repeated at the end of this period. Results: There was reduction in vitamin B12 levels with metformin with levels of 272.5pg/ml compared to 714.6pg/ml with other antidiabetics at the end of first period. The levels increased from 272.5pg/ml to 615.9 pg/ml at the end of second period after receiving the combination of metformin and mecobalamin. Conclusions: T2DM patients being treated with metformin had a greater risk of reduction in vitamin B12 levels and addition of vitamin B12 in the form of mecobalamin would decrease the reduction in vitamin B12 levels associated with Metformin therapy.